Cost analysis of initial highly active antiretroviral therapy regimens for managing human immunodeficiency virus-infected patients according to clinical practice in a hospital setting - Colombo GL; Castagna A; Di Matteo S; Galli L; Bruno G; Poli A; Salpietro S; Carbone A; Lazzarin A (Dove Medical Press, 2013)
Giorgio L Colombo,1,2 Antonella Castagna,3 Sergio Di Matteo,2 Laura Galli,3 Giacomo Bruno,2 Andrea Poli,3 Stefania Salpietro,3 Alessia Carbone,3 Adriano Lazzarin3,41Department of Drug Sciences, School of Pharmacy, University of Pavia, Italy; 2Studi Analisi Valutazioni Economiche (S.A.V.E.), Milan, 3Infectious Diseases Department, San Raffaele Hospital, Milan, 4Vita-Salute San Raffaele University, Milan, ItalyObjective: In the study reported here, single-tablet regimen (STR) versus (vs) multi-tablet regimen (MTR) strategies were evaluated through a cost analysis in a large cohort of patients starting their first highly active antiretroviral therapy (HAART). Adult human immunodeficiency virus (HIV) 1-naïve patients, followed at the San Raffaele Hospital, Milan, Italy, starting their first-line regimen from June 2008 to April 2012 were included in the analysis.Methods: The most frequently used first-line HAART regimens (>10%) were grouped into two classes: 1) STR of tenofovir disoproxil fumarate (TDF) + emtricitabine (FTC) + efavirenz (EFV) and 2) MTR including TDF + FTC + EFV, TDF + FTC + atazanavir/ritonavir (ATV/r), TDF + FTC + darunavir/ritonavir (DRV/r), and TDF + FTC + lopinavir/ritoavir (LPV/r). Data were analyzed from the point of view of the Lombardy Regional Health Service. HAART, hospitalizations, visits, medical examinations, and other concomitant non-HAART drug costs were evaluated and price variations included. Descriptive statistics were calculated for baseline demographic, clinical, and laboratory characteristics; associations between categorical variables and type of antiretroviral strategy (STR vs MTR) were examined using chi-square or Fisher's exact tests. At multivariate analysis, the generalized linear model was used to identify the predictive factors of the overall costs of the first-line HAART regimens.Results: A total of 474 naïve patients (90% male, mean age 42.2 years, mean baseline HIV-RNA 4.50 log10 copies/mL, and cluster of differentiation 4 [CD4+] count of 310 cells/µL, with a mean follow-up of 28 months) were included. Patients starting an STR treatment were less frequently antibody-hepatitis C virus positive (4% vs 11%, P=0.040), and had higher mean CD4+ values (351 vs 297 cells/µL, P=0.004) than MTR patients. The mean annual cost per patient in the STR group was €9,213.00 (range: €6,574.71-€33,570.00) and €14,277.00 (range: €5,908.89-€82,310.30) among MTR patients. At multivariate analysis, after adjustment for age, sex, antibody-hepatitis C virus status, HIV risk factors, baseline CD4+, and HIV-RNA, the cost analysis was significantly lower among patients starting an STR treatment than those starting an MTR (adjusted mean: €12,096.00 vs €16,106.00, P=0.0001).Conclusion: STR was associated with a lower annual cost per patient than MTR, thus can be considered a cost-saving strategy in the treatment of HIV patients. This analysis is an important tool for policy makers and health care professionals to make short- and long-term cost projections and thus assess the impact of these on available budgets.Keywords: HIV, HAART, single tablet regimen, pharmacoeconomics, multi-tablet regimen